Peri-Abortion Contraceptive Choices of Migrant Chinese Women: A Retrospective Review of Medical Records - Rose, Sally B.; Wei, Zhang; Cooper, Annette J.; Lawton, Beverley A. (PLOS ONE, 2012)
Background Migrant Asian women reportedly have low levels of contraceptive use and high rates of abortion in New Zealand. Chinese make up the largest proportion of migrant Asian in New Zealand. This study aimed to describe the contraceptive choices of Chinese women seeking abortion; to examine method choice in relation to demographic characteristics (including length of stay) and to determine whether Chinese women were over-represented among abortion clinic attendees. Methods Retrospective review of medical records at a public hospital abortion clinic involving 305 Chinese women. Previously collected data for European (n = 277) and Maori women (n = 128) were used for comparative analyses. Regression analyses explored correlates of contraceptive method choice. Population census data were used to calculate rates of clinic attendance across ethnic groups. Results Chinese women were not over-represented among clinic attendees, and had similar rates of contraceptive non-use pre-abortion as women in comparison groups. Use of the oral contraceptive pill by Chinese was lower pre-abortion than for other ethnic groups, but choice of this method post-abortion was similar for Chinese (46.9%, 95% CI 41–52.7) and European women (43.7%, 95% CI 37.8–49.7). Post-abortion choice of an intrauterine device did not differ significantly between Chinese (28.9%, 95% CI 23.8–34.3) and Maori women (37%, 95% CI 28.4–45.7), but was higher than uptake of this method by European women (21.7%, 95% CI 17–27.0). Age, parity and previous abortion were significant predictors of post-abortion method choice by Chinese women (p<0.05). Conclusions Following contraceptive counseling at the clinic, Chinese women chose more effective contraceptive methods for use post-abortion than they had used previously. As the population of migrant Chinese in New Zealand continues to increase, strategies are urgently needed to provide new arrivals with appropriate information and advice about contraception and where to access it, so women can be better prepared to avoid unplanned pregnancy.